Professional LAMP : Linux, Apache, MySQL, and PHP Web development - Naramore Elizabeth; Gerner Jason; Owens Morgan L.; Warden Matt (Indiana : Wiley Pub. Inc, 2006)
* The combination of Linux, Apache, MySQL, and PHP is popular because of interaction, flexibility, customization, and-most importantly-the cost effectiveness of its components
* Helps LAMP professionals take their skills to the next level with in-depth discussions of OOP; extensions of PHP such as PEAR, GD, XML, and CURL; improving site security; and advanced tools available to the coder
* Those proficient in other languages such as Java, C++, Perl and ASP will find this guide invaluable when transitioning to the LAMP environment
* The Web site includes sample scripts created in the course of each chapter, and several applications that can be modified and reused
Keywords: Web site development; Open source software